Relações teóricas da organização do conhecimento com as abordagens de catalogação de assunto, indexação e análise documental - Guimarães, José Augusto Chaves [UNESP]; Pinho, Fábio Assis [UNESP]; Ferreira, Gustavo Meletti [UNESP] (My University, 2012)
Considering knowledge organization and representation as a theoretical line used by Information Science to face the subject approach to information, in a dialogical relation with subject cataloguing, indexing and “analyse documentaire”, this article carries out a domain-analysis of Scire journal (1995-2010) in order to identify the scientific production in the mentionned theoretical lines as well as their relationships. Scire constitutes an environment where members of the different paradigms have found an space to relate each other.

Teniendo en cuenta la organización y representación del conocimiento como una orientación teórica apropiada por la Documentación para abordar el tratamiento temático de la información en una relación dialógica con otras corrientes como la catalogación de materias, indización y análisis de documentos, se procede a un análisis de dominio de la revista Scire (1995-2010) en lo que se refiere a la producción científica relativa a estas corrientes teóricas y a las interlocuciones existentes. La revista Scire demuestra ser un ámbito de relación entre ellas.
Relaciones teóricas de la organización del conocimiento con los enfoques de la catalogación de materias, indización y análisis de documentos: un análisis de dominio de la revista Scire (1995-2010)
Theoretical relationships among knowledge organization, subject cataloguing, indexing and “analyse documentaire”: a domain-analysis of Scire journal (1995-2010)
Keywords: Catalogação de assunto; indexação; Análise documental; organização do conhecimento; Análise de domínio